Cardiac magnetic resonance findings in acute myocarditis after mRNA COVID-19 vaccination. Issue 1 (July 2022) - Sano, Madoka; Murai, Ryosuke; Kim, Kitae; Furukawa, Yutaka
Abstract: There is increasing evidence for myocarditis as a complication of the mRNA coronavirus disease 2019 (COVID-19) vaccination. We report the case of a 20-year-old previously healthy man who presented with fever and chest pain 2 days after the second dose of mRNA-1273 vaccine. Electrocardiogram and laboratory studies showed extensive ST-segment elevation accompanied by elevated cardiac biomarkers. Cardiac magnetic resonance (CMR) revealed late gadolinium enhancement (LGE) characteristics of myocarditis. The patient rapidly improved with conservative management and was discharged on hospital day 6. As an advantage over previous reports, we performed a 1-month follow-up CMR. It showed improvement in myocardial edema but persistence of LGE which may indicate irreversible fibrosis. CMR may be useful not only for diagnosis but also for prognostic evaluation of myocarditis after COVID-19 mRNA vaccination. <Learning objective: With the expansion of coronavirus disease 2019 (COVID-19) vaccine administration, the number of cases of myocarditis as a complication has been increasing. Cardiac magnetic resonance imaging can be useful for the diagnosis and follow-up of patients with myocarditis after mRNA COVID-19 vaccination. Persistent late gadolinium enhancement may indicate irreversible myocardial fibrosis, and it is also associated with poor prognosis, similar to previously reported cases of other acute myocarditis.>